A 2007 Social Accounting Matrix for Botswana - van Seventer, Dirk (International Food Policy Research Institute, 2014)
A 2007 Social Accounting Matrix (SAM) for Botswana is constructed using data that available during the second half of 2011. This SAM is an update of the official 1996/7 SAM and a 2002/3 SAM by Thurlow (2007). Various data sources became available since these two SAMs were published, including data for the public sector, household income and expenditure, GDP data for aggregate and disaggregate industries, the national accounts, trade data and balance of payment data. The updated SAM provides a detailed representation of the Botswana economy. It separates 32 activities and 32 commodities; labor is disaggregated by 5 occupation groups; and households into 6 groups based on the rural/urban and income status of the household head. The SAM is a useful database for conducting economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.